Предмет: Алгебра,
автор: Ghostief
Упростите выражение: 3c-2/c+2 - c/c+2 : c/c^2-4 - 4c/c+2
Ответы
Автор ответа:
1
Ответ:
Объяснение:
3c-2/c+2 - c/c+2 : c/c²-4 - 4c/c+2=
=(3c-2)/(c+2) +c/(c+2) *(c^2-4)/c - 4c/(c+2)=
=(3c-2)/(c+2) + (c-2) - 4c/(c+2)=
=(3c-2+c²-4-4c)/(c+2)= (c+2)(c-3) / (c+2)= c-3
Похожие вопросы
Предмет: Алгебра,
автор: surname01112017
Предмет: Немецкий язык,
автор: kirakovalenko0102200
Предмет: Право,
автор: Аноним
Предмет: Информатика,
автор: nikolaystrelnikov
Предмет: Литература,
автор: artmon0408